THE RELATIONSHIP OF WEIGHT INCREASE, SEX DRIVE AND MENSTRUAL CYCLE WITH LONGER USE OF FP 3 MONTHS INJECTIONS IN TPMB ARI ROKHRIYANTI, S. KEB CAKUNG, EAST JAKARTA - Mustafa, Ayu Resky; Nenih, Nenih (HEARTY, 2025)
Background: One of the efforts to reduce the birth rate can be done through the use of contraceptives. One contraceptive that can be used is DMPA (Depo -medroxyprogesterone Acetate) or depo provera or better known as 3-month injection contraception, the name for the use of 3-month contraception. months often cause side effects, one of the side effects is weight gain, irregular menstrual cycles, and decreased sex drive. Objective: of this research is to determine the relationship between weight gain, sexual desire and menstrual cycle with the duration of using injectable contraceptives for 3 months in PMB Bd. Ari Rokhriyati, S. Keb, Cakung East Jakarta in 2023. Method: This research uses descriptive quantitative methods. The population in this study were all 3-month injection contraceptive acceptors who visited PMB Bd. Ari Rokhriyati, S. Keb, Cakung, East Jakarta for the period September - November 2023 as many as 359 people. With a total sample of 76 mothers who use family planning, the sampling technique used purposive sampling. The dependent variable is 3 month KB users. The independent variables are weight gain, sex drive and menstrual cycle. Data collection uses observation sheets. Statistical tests use the chi square test. The results of this study show a relationship between the menstrual cycle and the duration of family planning use of 3 months in PMB Bd. Ari Rokhriyati S. Keb Cakung Jakarta with a p-value = 0.002 (p < 0.05). The duration of using family planning for 3 months has an effect on sexual arousal with a p-value = 0.008 (p < 0.05). Meanwhile, the duration of using family planning for 3 months does not have an effect on weight gain with a value of p = 0.239 (p > 0.05). Conclusion: Using contraception for 3 months affects the menstrual cycle, sexual desire and weight gain.